SIMULATION OF THE PROCESS OF PROFESSIONAL COMPETENCE FORMATION OF FUTURE ELECTRICAL TECHNICIANS IN AGRICULTURAL COLLEGES (Innovative professional education, 2023)
The tasks of improving the quality of professional training of specialists in agricultural colleges are determined by modeling the process of forming the professional competence of future electrical technicians for a more detailed study of the structural and functional features of the phenomenon. The model for the formation of the professional competence of future electrical technicians consists of components of a generalized nature, which in their own form can be considered as subsystems that are integrated from individual components. The interconnection of the system elements and the integrity of the process of forming the professional competence of future electrical technicians is ensured by relying on regularities, trends and ideas aimed at ensuring the unity and completeness of the generalized components. The model includes methodological-target, subject, content-technological and diagnostic-resultative blocks.
Keywords: model, modeling, professional competence, future electricians, agricultural colleges